2013
DOI: 10.1109/tcomm.2013.032013.120601
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Generalized DF-CF for Gaussian Relay Channels: Decode or Compress?

Abstract: Abstract-We consider a three-node quasi-static communication system with a full-duplex relay. The goal is to determine the relaying mode that enables rate-efficient communication under given channel conditions. To achieve this goal, we consider a generalized scheme that subsumes the decode-and-forward (DF) and compress-and-forward (CF) schemes as special cases. The generalized scheme is considered when the source and relay signals are synthesized from commonly-used Gaussian codebooks, which are shown to be cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…One can reformulate (35) as (24). As K * is the solution of (24), It is not hard to write T II as (23) following from the definition of K.…”
Section: Appendix D Proof Of Theorem 45mentioning
confidence: 99%
See 1 more Smart Citation
“…One can reformulate (35) as (24). As K * is the solution of (24), It is not hard to write T II as (23) following from the definition of K.…”
Section: Appendix D Proof Of Theorem 45mentioning
confidence: 99%
“…In static channel gain case, CF was superposed on DF in [7], leading to a positive rate gain [23]. This superposition scheme was thoroughly investigated in [24] and [25].…”
Section: Introductionmentioning
confidence: 99%
“…The rate achieved by DF and CF strategies for full-duplex relay channel was presented in [1]. With more complicated coding structures and decoding proce dures, it was found that combining DF and CF strategies can achieve a larger rate [1] [2][3] [4]. Due to the generality of DF and CF strategies, they have been adopted in complicated relay networks, achieving capacity asymptotically [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Following the equal-time-phase assumption and fixed source power assumption, the rate functions are specified as [7] RD F( P2) � � max min {C(h�lPd + C( (Ip 2 )h�lPl) ' 2 o :S;p9 C( h�lPl) + C( h�lPl + 2h�2P2 + 2ph3lh32,/2PlP2)} (4) l; 1 2 RCF(P2) = "2 C( h 3l Pl)+ � C(h 2 P 2h�lPlh�2P2…”
mentioning
confidence: 99%
“…show that, under Rayleigh fading channel conditions, this selection yields significant gains over fixed DF and CF. The work in this chapter was published, in part, in [12] and [13].…”
Section: Optimization-based Approachmentioning
confidence: 99%